2016
DOI: 10.2196/jmir.6349
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Health Information Technology Adoption: The Potential for a New Digital Divide

Abstract: BackgroundApproximately one-half of American adults exhibit low health literacy and thus struggle to find and use health information. Low health literacy is associated with negative outcomes including overall poorer health. Health information technology (HIT) makes health information available directly to patients through electronic tools including patient portals, wearable technology, and mobile apps. The direct availability of this information to patients, however, may be complicated by misunderstanding of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
268
3
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(291 citation statements)
references
References 29 publications
8
268
3
12
Order By: Relevance
“…Further research should attempt to replicate and/or refine the developed typology, ideally with health-related dimensions by including more specific constructs around health literacy and health-related self-efficacy [7,46,47]. recommendations [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research should attempt to replicate and/or refine the developed typology, ideally with health-related dimensions by including more specific constructs around health literacy and health-related self-efficacy [7,46,47]. recommendations [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving health outcomes depends on enablers around internet skills [5][6][7], particularly in terms of making sense of information quantity and quality [8] and health literacy in the sense of being able to translate the findings into health-promoting behaviours [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[37] Another study also showed that older adults were less likely than younger adults to value the importance of Patient Health Records (PHRs). [31] There might be several reasons behind these findings including: a) greater ease of use and comfort with technology among younger adults, [38] b) poor usability, availability, and accessibility of HIT functions tailored to the elderly, [39][40][41] c) lower health literacy in the elderly, [42,43] d) lower educational attainment and income in the elderly, [3,44] and e) unique challenges from having chronic diseases that are more prevalent in the elderly that impede use of technology (e.g. arthritis, vision impairment etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have characterized app privacy policies as being lengthy, linguistically complex, and even absent [8,9]. They have been shown to be difficult to read even for people pursuing a graduate degree in law or policy [10].…”
Section: Introductionmentioning
confidence: 99%
“…One study suggested that those with lower health literacy might misjudge privacy policies and falsely assume more protections are in place than those who are more health literate [9]. However, little research has been done to examine the reading level required to understand mobile health app privacy policies.…”
Section: Introductionmentioning
confidence: 99%